Pendampingan Pengembangan Produk Baru Kerajinan Kulit Ikan Pari untuk Meningkatkan Daya Saing Usaha di Pasar Ekspor - Nurwidiana, Nurwidiana; Asyhari, Asyhari; Farisa, Sam (Community Empowerment, 2018)
Launching a new product is important to improve the company’s competitiveness and revenue. White Blue is expanding its business by producing finished product for international market. Mentoring activities are conducted for developing product. There are seven stages for product development. The Handmade product concept is selected from the idea generation stage. Web based marketing will be applied for the marketing strategy. Mentoring activities are continued to attain the concept of product development. Training in production processes is providing for handmade methods according to the concept of selected product. Procurement of handmade production equipment is made to support production processes. Marketing training for web based marketing methods is given to support marketing so that the product of SMEs can be exported. The result of mentoring and training activities are: 1) SME’s has the concept of product development, namely handmade product, 2) SME’s has resources to produce handmade product, there are human resources, machinery and equipment, 3) The existence of online marketing the export market for SME’s is increasing.